Receptor Inhibition of Pheromone Signaling Is Mediated by the Ste4p G(β) Subunit - Kim, Jinah (American Society for Microbiology, 1999)
The pheromone response pathway of the yeast Saccharomyces cerevisiae is initiated in MATa cells by binding of α-factor to the α-factor receptor. MATa cells in which the a-factor receptor is inappropriately expressed exhibit reduced pheromone signaling, a phenomenon termed receptor inhibition. In cells undergoing receptor inhibition, activation of the signaling pathway occurs normally at early time points but decreases after prolonged exposure to pheromone. Mutations that suppress the effects of receptor inhibition were obtained in the STE4 gene, which encodes the β-subunit of the G protein that transmits the pheromone response signal. These mutations mapped to the N terminus and second WD repeat of Ste4p in regions that are not part of its G(α) binding surface. A STE4 allele containing several of these mutations, called STE4(SD13), reversed the signaling defect seen at late times in cells undergoing receptor inhibition but had no effect on the basal activity of the pathway. Moreover, the signaling properties of STE4(SD13) were indistinguishable from those of STE4 in wild-type MATa and MATα cells. These results demonstrate that the effect of the STE4(SD13) allele is specific to the receptor inhibition function of STE4. STE4(SD13) suppressed the signaling defect conferred by receptor inhibition in a MATa strain containing a deletion of GPA1, the G protein α-subunit gene; however, STE4(SD13) had no effect in a MATα strain containing a GPA1 deletion. Suppression of receptor inhibition by STE4(SD13) in a MATa strain containing a GPA1 deletion was unaffected by deletion of STE2, the α-factor receptor gene. The results presented here are consistent with a model in which an a-specific gene product other than Ste2p detects the presence of the a-factor receptor and blocks signaling by inhibiting the function of Ste4p.